The International Legal Framework to Protect Children in Armed Conflict - MERMOUNE, Rachida (Journal of Human Sciences, 2016)
The core elements of the international legal framework are strong tools for the protection of children affected by armed conflict. However, there are other tools which have not been discussed in this introduction, such as the Ottawa Convention and the European Union Guidelines on Children and Armed Conflict, which can contribute to protection.Implementation of this framework needs continued investment in terms of national legislation and allocation of sufficient resources with the involvement of the many agencies such as NGOs, the Special Representative, the Security Council and other UN agencies. This investment should not be limited to children associated with armed forces or armed groups, but instead should include the protection, recovery and reintegration of all children affected by armed conflict, as required under the ACRWC and the CRC.Special attention is given to remedies for children’s rights violations—for example, through truth and reconciliation commissions at the national and international level, and the prosecution of perpetrators of crimes against children via special courts and tribunals, and the ICC. The Third Optional Protocol to the CRC providing communications procedure can become an extra tool for remedies.